Croatia: Global and European Influence on Procedural Tax Provisions - Žunić Kovačević, Nataša (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
After short introduction on the impact of European and global recent changes on the development of Croatian tax law it is given a survey on the issue of the concept of tax sovereignty in Croatia. Special part of the paper is the section that confirms influence and the importance of the tax harmonization at the EU level for national legislative amendments and reforms. The obvious field of such influence is revised in section on anti-tax avoidance framework with examined national tax policy in the area of tackling tax avoidance and fraud. Special focus is given on the implementation and evaluation of Union measures in the field of anti-tax-avoidance in Croatia, since the EU policing tax avoidance has special dimension for MS. Information exchange and mandatory disclosure rules as tools for fighting tax avoidance and fraud are fields that are shown as example of the influence of tax policy approach addressing the issues of tax transparency and fighting tax evasion. Peculiarities in the domestic legislation as rules that apply in addition to EU law are in a brief analysed in paper, such as the introduced piercing the corporate veil for tax purposes. It was an instrument for preventing tax avoidance. It is concluded that Croatian tax legislation landscape would undeniably benefit from further improvements, especially regarding tax procedure, and improvements from the European and international level. Croatian tax system in the last decades have been linked with the inputs and advice of foreign experts so it is underlined that Croatian, as any tax system, should be adapted to country’s socio-economic specificities. Keywords: tax sovereignty, tax harmonization, European and global impact, Croatian tax law, national legislative amendments and reforms